OPTIMALISASI PRODUKSI PADA MEBEL MAHAKAM SAMARINDA - HANDOYO, AHMAD BUDI (EKONOMIA, 2013)
Ahmad Budi Handoyo , furniture production optimization Mahakam Samarinda , under the guidance of Mrs. Dra.Elfreda A. Lau , Msi and Mr. Heriyanto , SE , MM.To find furniture production optimization conducted an analysis beforehand . In connection with the problem that arises is whether the production of furniture in the furniture business in the Mahakam Samarinda were optimal profit , the author tries to analyze the production of furniture in the furniture business Mahakam Samarinda using the simplex method and linear program (Linear Programming) .         In this report the authors found the hypothesis of the existing problems of " alleged that the production of furniture in the furniture business Mahakam Samarinda not optimal " . For this analysis , the necessary production data in the form of production volume and production costs . Basic theory used is production management with analytical tools Linear Programming (Linear Programming) using the simplex method .         Based on the discussion of the results and conclusions of this study :         From the results of calculations using analytical tools such as linear programming simplex method , it can be seen that the combination of furniture production, furniture business Mahakam Samarinda has not been optimal , because the amount is not yet memeiliki production for maximum profit . Mahakam Samarinda furniture business before producing furniture with 145 units and a number of cabinet office desk 155 units , if the profit is calculated Rp.70.000.000 , 00 and reduced taxes to Rp.63.000.000 , 00.         However the raw materials and labor with available calculated through analytical tools acquired production numbers obtained are as many as 155 units of cupboards and counter kantr 150 units , if the profit is calculated Rp.72.000.000 , 00 and minus taxes be Rp.64.800.000 .         It is known that the amount of production when analyzed with linear programming , cabinets up 10 units to 155 units amounting to 6.89% , but the amount of production that can be produced office desk down by 5 units to 150 units , having penerununan of 3.22 % . And profit-making analysis obtained after getting an increase of Rp.1.800.000 , 00 if the calculated percent increase is 2.86% . Then the amount of furniture production in Mahakam Samarinda Furniture business in 2008 is not optimal because ushama Menel Mahakam Samarinda can produce furniture with more cupboard units 10 units amounted to 115 units , and reduce the production of office desks by 5 units to 150 units . The benefits could be even greater Rp.1.800.000 , 00 became Rp.64.800.00 , 00 from the entire discussion above, the authors put forward a hypothesis that has been proven and accepted.